Occupational therapy : principles and practice - Punwar, Alice J., ....-; Peloquin, Suzanne M., ....- (Philadelphia : Lippincott, Williams and Wilkins, 2000)
Contents: --------- AN OVERVIEW OF OCCUPATIONAL THERAPY 1. Defining ocuupational therapy 2. The philosophy of occupational therapy 3. The development of occupational therapy 4. Occupation as therapy: activity as a therapeutic tool PREPARING FOR PRACTICE 5. Professional education and credentialling patterns 6. Roles and functions of the occupational therapist and the ocuupational assistant THE WORLD OF OCCUPATIONAL THERAPY PRACTICE 7. Understanding health care in the US 8. The art and science of practice 9. The spirit and the works of teams 10. Psychosocial practice 11. Practice in the acute care hospital 12. Adult rehabilitation practice 13. Developmental disabilities practice 14. Public school practice 15. Elder care 16. Practice in home health care 17. Lifework in occupational therapy : advanced career choices PROFESSIONAL RESOURCES AND CONTEMPORARY TRENDS 18. Occupational therapy organizations 19. International occupational therapy 20. Contemporary issues and trends
Keywords: Ergotherapie